Peran Lembaga Pemberdayaan Masyarakat Kelurahan Gayam sebagai Perwujudan Good Governance Ditinjau dari Peraturan Daerah Kabupaten Sukoharjo Nomor 6 Tahun 2009 Tentang Lembaga Kemasyarakatan Kelurahan - Sari, Cindy Amalia; Firdausy, Adriana Grahani (Res Publica: Jurnal Hukum Kebijakan Publik, 2021)
ABSTRACTCommunity Empowerment Institution is the implementation of good governance formed on community initiatives. Good governance as a tool to avoid abuse of power in every government policy, but its implementation in Indonesia is not optimal due to the lack of economic and socio-cultural empowerment. The purpose of this study is to analyze the role of the Gayam Village Community Empowerment Institution as a manifestation of good governance in terms of the Sukoharjo District Regulation Regarding Village Social Institutions and the inhibiting and supporting factors of the implementation of this role. The results showed that the role of the Gayam Village Community Empowerment Institution has ensured the implementation of the elements of accountability and participation as well as alleviating the burden on the Gayam Village community. The supporting factors for this role are: (i) mutual cooperation and (ii) effective, while the inhibiting factors are: (i) creativity, (ii) media use, and (iii) human resources.Keywords : community empowerment institutions; good governance; district  regulation.